2022
DOI: 10.1158/2326-6066.cir-22-0197
|View full text |Cite
|
Sign up to set email alerts
|

NET-Triggered NLRP3 Activation and IL18 Release Drive Oxaliplatin-Induced Peripheral Neuropathy

Abstract: Oxaliplatin is an antineoplastic agent frequently used in the treatment of gastrointestinal tumors. However, it causes dose-limiting sensorimotor neuropathy, referred to as oxaliplatin-induced peripheral neuropathy (OIPN), for which there is no effective treatment. Here, we report that the elevation of neutrophil extracellular traps (NETs) is a pathological change common to both cancer patients treated with oxaliplatin and a murine model of OIPN. Mechanistically, we found that NETs trigger NLR family pyrin dom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Besides, intraarticular injection NETs reduced the mechanical threshold in mice and joint hyperalgesia induced by NETs was prevented in mice deficient for Tlr 4 and Tlr 9 [ 63 ]. Moreover, eicosapentaenoic acid alleviated the hyperalgesia in oxaliplatin-induced peripheral neuropathy mice by inhibiting NETs formation and then abolishing NLR family pyrin domain containing 3 (NLRP3) inflammasome activation [ 64 ]. Therefore, NETs triggered by IL-17 may cause hyperalgesia through Toll-like receptor (TLR)-4, TLR-9 or activation of NLRP3.…”
Section: Peripheral Mechanisms Of Il-17 In Pathological Painmentioning
confidence: 99%
“…Besides, intraarticular injection NETs reduced the mechanical threshold in mice and joint hyperalgesia induced by NETs was prevented in mice deficient for Tlr 4 and Tlr 9 [ 63 ]. Moreover, eicosapentaenoic acid alleviated the hyperalgesia in oxaliplatin-induced peripheral neuropathy mice by inhibiting NETs formation and then abolishing NLR family pyrin domain containing 3 (NLRP3) inflammasome activation [ 64 ]. Therefore, NETs triggered by IL-17 may cause hyperalgesia through Toll-like receptor (TLR)-4, TLR-9 or activation of NLRP3.…”
Section: Peripheral Mechanisms Of Il-17 In Pathological Painmentioning
confidence: 99%
“…Although so far, little evidence is available to investigate the relations between NETs and inflammasome. However, it was recently reported that NETs could trigger the NLRP3 inflammasome activation and IL-18 secretion release during the occurrence of oxaliplatin-induced peripheral neuropathy (OIPN) via the induction of the LPS-toll-like receptor 4 (TLR4)-JNK pathway ( Lin et al, 2022 ). However, to further explore the crosstalk between NETs and inflammasome, more studies are demanded for investigation.…”
Section: Part I: Biological Features Of Netsmentioning
confidence: 99%
“…At the same time, the average urinary excretion rate of LBP in 24 hours was as high as 70%, suggesting that LBP is rapidly cleared by the kidneys, does not accumulate easily in the body, has a short duration of action, and has mild adverse reactions ( 21 ). LBP has no obvious nephrotoxicity, ototoxicity, or neurotoxicity, and has significantly less gastrointestinal toxicity ( 22 ).…”
Section: Introductionmentioning
confidence: 99%